2022
DOI: 10.1029/2021jd035342
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of VOC Composition at Urban and Suburban Sites of New Delhi, India in Winter

Abstract: Volatile organic compounds (VOCs) are ubiquitous organic gases present in the Earth's atmosphere at trace levels (pptv-ppbv). Typically, VOCs are categorized into two major groups of non-methane hydrocarbons (NMHCs) and oxygenated-VOCs (OVOCs). NMHCs are primary VOCs emitted from biogenic and anthropogenic sources,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 162 publications
1
5
0
Order By: Relevance
“…2k). Simulated isoprene is in agreement with diurnal observations in Delhi (Tripathi et al, 2022) and in accordance with observed mean level in Leicester (Sommariva et al, 2021). The nitrate radical (NO 3 ), which is a nighttime oxidant, is formed through reaction between NO 2 and O 3 (G36).…”
Section: Box Model Setupsupporting
confidence: 85%
“…2k). Simulated isoprene is in agreement with diurnal observations in Delhi (Tripathi et al, 2022) and in accordance with observed mean level in Leicester (Sommariva et al, 2021). The nitrate radical (NO 3 ), which is a nighttime oxidant, is formed through reaction between NO 2 and O 3 (G36).…”
Section: Box Model Setupsupporting
confidence: 85%
“…VOC/NO x ratio was 1.8 in contrast to a ratio of 0.4 for traffic emissions. Greater reductions of VOCs suppress the increase in O 3 in Delhi, which is a VOC-limited environment [88][89][90]. However, the O 3 formation regime may vary for different sites within Delhi depending on VOCs/NO x [28,91].…”
Section: Challenges and Mitigation Pathways For Co-controlling Pm 25 ...mentioning
confidence: 99%
“…The PTR-TOF-MS is widely used for measuring NMVOCs with high mass resolution and sensitivity. A detailed description of the instrument can be found in other studies (Graus et al, 2010;Jordan et al, 2009;Tripathi et al, 2022;Tripathi and Sahu, 2020), while a brief description is given here. The PTR-TOF-MS is based on the chemical ionisation method, facilitated by proton-transfer reactions with hydronium (H3O + ) ions as the primary reactant ion, which causes much less fragmentation of organic molecules in the sampled air.…”
Section: 2mentioning
confidence: 99%
“…The calibration of the instrument was performed at the starting, middle and end of the campaign using a certified standard gas mixture (L5388, Ionicon Analytik GmbH Innsbruck, with a stated accuracy better than 8%) containing ~1.0 ppmv of VOCs. A 145 detailed description of the similar set-up and unit is given in the previous studies (Jain et al, 2022;Tripathi et al, 2022). The exact mass-identified chemical formula and family of species of the observed NMVOCs (173 in number) is given in supplementary Table S1.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation